2018
DOI: 10.1073/pnas.1721916115
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, evolution, and functions of DNA phosphorothioate epigenetics in bacteria

Abstract: The chemical diversity of physiological DNA modifications has expanded with the identification of phosphorothioate (PT) modification in which the nonbridging oxygen in the sugar-phosphate backbone of DNA is replaced by sulfur. Together with DndFGH as cognate restriction enzymes, DNA PT modification, which is catalyzed by the DndABCDE proteins, functions as a bacterial restriction-modification (R-M) system that protects cells against invading foreign DNA. However, the occurrence of systems across a large number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(150 citation statements)
references
References 41 publications
(44 reference statements)
4
131
1
Order By: Relevance
“…Nitrosopumilus salaria also encode this DNA modification system. These genes possibly encode a primitive immune system by enabling discrimination between self and non-self DNA (but can also epigenetically affect the transcriptome of bacteria; Tong et al 2018) and might thusin concert with the better understood canonical RM systems (Fig. S6)be particularly useful for sponge symbionts living in a system where they are prone to genetic exchanges.…”
Section: Mixotrophy Of Thaumarchaeotamentioning
confidence: 99%
“…Nitrosopumilus salaria also encode this DNA modification system. These genes possibly encode a primitive immune system by enabling discrimination between self and non-self DNA (but can also epigenetically affect the transcriptome of bacteria; Tong et al 2018) and might thusin concert with the better understood canonical RM systems (Fig. S6)be particularly useful for sponge symbionts living in a system where they are prone to genetic exchanges.…”
Section: Mixotrophy Of Thaumarchaeotamentioning
confidence: 99%
“…Unlike methylation‐based R‐M systems, DNA PT modification is only partial at a given site in a population of cells, even at the presence of the active restriction cognate DndFGH, indicating alternative roles of PT . Later studies by Tong et al demonstrated that PT modification is a versatile player in DNA epigenetic control and the maintenance of cellular redox homeostasis in Pseudomonas fluorescens . Taken together, these applications demonstrate that SMRT sequencing offers a powerful approach for exploring pervasive and diverse epigenetic markers, to determine the targets of methyltransferases or other modifying enzymes and provide insight into the effects of such modifications on biological processes.…”
Section: Applications Of Smrt Sequencing In Bacterial Epigeneticsmentioning
confidence: 96%
“…Distinct from the methylation of nucleobases, DNA phosphorothioate (PT) modification is a newly identified type of epigenetic modification in which the non‐bridging oxygen in the sugar‐phosphate backbone is substituted with sulfur in a sequence‐selective and R P stereo‐specific manner . In addition to being a component of restriction‐modification (R‐M) systems, Tong et al reported that PT modification is involved in the epigenetic regulation of gene expression and maintenance of cellular redox homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Leonard et al reported that different donor‐derived strains of the same species have inconsistent Dam methylation patterns, which might be a potential indicator for disease statues. Furthermore, considering the important physiological function of DNA phosphorothioation (PT) modification, analysis of PT modification of the intestinal microbiome may also deepen the understanding of its diversity. Diet and other environmental factors may alter the microbial environment in the host, but because of the functional redundancy across taxonomy, differences in compositional structure, especially at higher taxonomic levels, do not indicate altered microbiota‐host interactions.…”
Section: Gut Microbiota‐based Diagnosis and Therapiesmentioning
confidence: 99%